Corrections of chemical assays in a series of binding nodes by lagrange multipliers - Pérez Matos, Edgar Ademar (2009)
The present work will display sequential steps in order to obtain correct of the chemical assays in the flows of a series of nodes (cells). Basonat function through widespread; who is perfectly suited to the analysis of the processes of industrial nature float in mineral processing. Where obtained the assay valves (metal content) of the chemical analysis has already been made are appropriate to their respective correction; who involves a whole procedure since its flow diagram, its laws; for then to calculate the standardized flows, the Lagrange multiplier (optimizer for errors), and the corrections that finally lead to the desired.